PROSPEK PENGEMBANGAN HOME INDUSTRI GETUK PISANG DALAM MENGHADAPI PANDEMI COVID-19: SEBUAH ANALISIS NILAI TAMBAH - Uyun Luthfiana; Ati Kusmiati (JSEP (Journal of Social and Agricultural Economics), 2022)
The Covid-19 pandemic in 2020 had a bad impact and caused various businesses to experience many declines and even losses. Business actors carry out various ways to survive and save their businesses from bankruptcy. This study aims to determine the added value, income, and development strategy. The method in this study used descriptive and analytical methods. The sampling method in this research is the purposive sampling technique. Analysis of the data used is added value, income analysis, SWOT analysis, and QSPM. The results showed that the Getuk Pisang Home Industry in Kediri Regency during the Covid-19 pandemic in processing bananas into Getuk Pisang products had positive added value. During the Covid-19 pandemic, the income received by the Getuk Pisang Home Industry experienced a very drastic decline when compared to the income before the Covid-19 pandemic. The results of the SWOT analysis show that the position of the Home Industry during the Covid-19 pandemic is in quadrant II, namely the diversification strategy, where companies must use strengths to take advantage of long-term opportunities. The SWOT matrix produces several alternative strategies that will determine the attractiveness of the data on the QSP matrix. The highest TAS (Total Attractive Score) value in the QSP matrix is 7.42, with optimizing internet media to increase sales of Getuk Pisang during the pandemic.